Minimization for LED-backlit TFT-LCDs - Cheng, Wei-Chung; Chao, Chain-Fu (Proceedings of the 43rd annual Design Automation Conference, 2006)
This paper presents an algorithm for minimizing power consumption of LED backlights in transmissive TFT-LCD monitors. The proposed algorithm reduces power consumption by scaling the luminous intensity of the red, green, and blue LED backlights independently according to the image histograms of each color channel. The algorithm consists of two phases. The first phase, chromaticity scaling, finds the optimal ratios of red, green, and blue backlights subject to a perceived color difference constraint. The second phase, luminance scaling, finds the optimal dimming factor subject to a perceived lightness difference constraint. The perceived color and lightness differences are measured by the CIELAB Color Difference Equation 2ΔE*ab, a standard metric for measuring color variation. Psychophysical experiments were performed with 35 observers to uncover the optimal luminance scaling function. An experimental LED backlight module was implemented and installed on a 19" side-lit TFT-LCD monitor to replace the original CCFL backlight. Within limited perceivable difference 2ΔE*ab, up to 76% of power consumption can be reduced for the benchmark images.